Economic empowerment in the framework of State Defense in Bandung District Islamic boarding schools - Yulivan, Ivan (Technium Social Sciences Journal, 2022)
Radicalism and Terrorism are still real and potential threats. There are many reasons why people can be exposed, one of which is the low economy of the community. Islamic boarding school educational institutions, so far, their economic resources sometimes come from donor funds, infaq, monthly students, and self-help educators. The economic potential of Islamic boarding schools in Indonesia is very large, it is hoped that with good management it can increase income so that the boarding school continues to exist in producing intellectual cadres as well as improving the economy of the surrounding community. By empowering MSMEs, they can become the driving force of the people's economy that continuously contributes to the prosperity and independence of the nation's economy. Indirectly, MSMEs are also a form of effort to manage strategic resources during peacetime in order to face threats to territorial integrity, state sovereignty and the safety of all nations in realizing national security. This study aims to analyze the empowerment of the Al-Ittifaq Islamic Boarding School in Bandung Regency in increasing income and developing teaching in order to encourage pesantren independence in supporting the defense economy. This study uses descriptive qualitative research methods. This research data collection technique is interview, observation, and literature study. The data obtained were then analyzed based on data analysis according to Miles, Huberman, and Saldana. The results showed that Pesantren Al-Ittifaq has an integrated and structured empowerment model, namely economic and business education as well as gradual, continuous, and synergistic empowerment, as well as the strength of a strong inter-element network on the principle of kinship. Fostering the economic independence of students at the Al-Ittifaq Islamic Boarding School is to involve students in economic endeavors. By providing basic training so that they become skilled workers. Thus there is a transformation of applied science (technical skills) to the students as a form of coaching to build a spirit of independence and entrepreneurship.